Epidemiologic and clinical profile of burns in a tertiary hospital in Sub-Saharan Africa - N.A. Forbinake; G. Dongmo; C.S. Ohandza; A. Chichom-Mefire; P. Fokam; G. Beyiha (Elsevier, 2020)
Background: Burns are a serious public health problem accounting for 265 000 annual death from fires alone worldwide. Over 96% of fatal fire-related burns occur in low- and middle-income countries. This study is aimed at describing the demographic characteristics, clinical presentation, burn causes, delay to presentation, place of occurrence and circumstances under which the patients were burned. Methods: It was a retrospective observational study carried out from the 1st of January 2008 to the 31st of December 2015 in the Burn Unit of the Douala General Hospital. An adapted questionnaire was used for which information on age; sex and clinical presentation were recorded. Data was transferred to Microsoft Excel 2015 and Statistical Package for Social Sciences (SPSS) version 20.0 for data analysis. Results: Of 453 patients studied, there was a male predominance (n = 281, 63.9%) and a mean age of 25.2 ± 17.8 years. Many patients (n = 183, 40.4%) came within an hour after being burned and flame burns were the commonest (n = 170, 37.3%) frequently arising from domestic gas accidents (n = 69, 15.2%). The majority of patients (n = 203, 44.8%) had burns affecting 1-9% of the total body surface area and 2nd degree burns were the commonest form of burn depth (n = 225, 50.1%). The mean length of hospital stay was 26.3 ± 12.2 days. Conclusion: Burns occur mostly in male adults of 25.2 years with flames being the main burn agent. The patients usually have 2nd degree burns, the majority had burns >10% of burn surface area and most patients arrived at the hospital within an hour. When admitted, hospitalisation averagely lasts 26.3 days. Keywords: Burns, Epidemiology, Diagnosis, Africa South of the Sahara